Divided attention: An undesirable difficulty in memory retention. - Gaspelin, Nicholas; Ruthruff, Eric; Pashler, Harold (Memory & Cognition, 2013)
How can we improve memory retention? A large body of research has suggested that difficulty encountered during learning, such as when practice sessions are distributed rather than massed, can enhance later memory performance (see R. A. Bjork & E. L. Bjork, ). Here, we investigated whether divided attention during retrieval practice can also constitute a desirable difficulty. Following two initial study phases and one test phase with Swahili-English word pairs (e.g., vuvi-snake), we manipulated whether items were tested again under full or divided attention. Two days later, participants were brought back for a final cued-recall test (e.g., vuvi-?). Across three experiments (combined N = 122), we found no evidence that dividing attention while practicing retrieval enhances memory retention. This finding raises the question of why many types of difficulty during practice do improve long-term retention, but dividing attention does not.